Long-term adaptation of Bacillus subtilis 168 to extreme pH affects chemical and physical properties of the cellular membrane - Petrackova, Denisa; Vecer, Jaroslav; Svobodova, Jaroslava; Herman, Petr (The Journal of membrane biology, 2010)
We characterized physical and chemical properties of cell-membrane fragments from Bacillus subtilis 168 (trpC2) grown at pH 5.0, 7.0 and 8.5. Effects of long-term bacterial adaptation reflected in growth rates and in changes of the membrane lipid composition were correlated with lipid order and dynamics using time-resolved fluorescence anisotropy of 1,6-diphenyl-1,3,5-hexatriene. We demonstrate that the pH adaptation results in a modification of a fatty acid content of cellular membranes that significantly influences both the lipid-chain order and dynamics. For cultivation at acidic conditions, the lipid order increases and membrane dynamics decreases compared to pH 7.0. This results in rigid and ordered membranes. Cultivation at pH 8.5 causes slight membrane disordering. Instant pH changes induce qualitatively similar but smaller effects. Proton flux measurements performed on intact cells adapted to both pH 5.0 and 8.5 revealed lower cell-membrane permeability compared to bacteria cultivated at pH optimum. Our results indicate that both acidic and alkalic pH stress represent a permanent challenge for B. subtilis to keep a functional membrane state. The documented adaptation-induced adjustments of membrane properties could be an important part of mechanisms maintaining an optimal intracellular pH at a wide range of extracellular proton concentrations.
Keywords: Diphenylhexatriene; Bacillus subtilis; fluorescenční polarizace; koncentrace vodíkových iontů; difenylhexatrien; Cell Membrane; Hydrogen-Ion Concentration; Fluorescence Polarization; buněčná membrána